(untitled) (International Conference on Computers in Education, 2016)
We describe an observational investigation that explores whether creating open social student models using software metrics promotes reflection. Metric visualisations were shown to six groups in an undergraduate software engineering project course. Seeing their own visualisations prompted reflection on their codebase at a conceptual level as expected; this is as predicted by previous research. When viewing other’s visualisations, the focus changed to comparative statements with reasoning to explain differences showing that this increased performance orientation. Delayed queries showed that engagement was varied but increased in all groups.